OPTIMIZING THE USE OF SOCIAL MEDIA AS MARKETING MEDIA FOR MSMEs IN BANYUASIN DISTRICT - Purba, Andi Ricardy; Nyoman Surya Utama, I Gusti; Sudin, Sudin (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Social media has become an important tool for businesses to market their brands and reach a wider audience. Social media optimization is the process of improving social media strategies to achieve better results, such as faster follower growth and increased interaction with potential consumers. In this community service activity, the author discusses and conveys the importance of optimizing the use of social media for marketing and provides several tips for achieving this to MSME entrepreneurs in the Banyuasin sub-district. This community service activity was attended by 35 entrepreneurs in the culinary, accessories and fashion fields in the Banyuasin sub-district. This activity lasted 2.5 hours, starting with a presentation by each author, then presenting examples of the application of marketing on social media, and ending with a discussion session that very much aroused the enthusiasm of the participants about optimizing social media in MSME operations. Community service like this must continue to be carried out to increase public awareness that digitization can increase efficiency in business and can increase MSME sales.